THE ALGORITHM IMPLEMENTATION THE TECHNIQUES OF REORGANIZATION AS A MANAGEMENT TOOL OF FINANCIAL SOUNDNESS OF A CREDIT INSTITUTION - Z. Patladze (Вестник университета)
In the article the algorithm implementation, the techniques of reorganization as a management tool of financial soundness of a credit institution, taking into account international experience and modern Russian realities.